The relationship between R&D intensity and profit-sharing schemes: evidence from Germany and the United Kingdom - Diego d'Andria; Silke Uebelmesser (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We study the determinants of the use of profit sharing schemes (PSS) by exploiting two datasets for Germany and the United Kingdom. Our results replicate studies for the U.S. which report a positive correlation between R&D activity and PSS use. For Germany, Granger-causality tests support a causal interpretation. Similarly to U.S.-based studies, we also find that a firm's turnover is strongly associated with PSS use whereas this does not hold for the age of a firm and its organizational characteristics.
Keywords: L20; J33; O31; 330